Improved Dysphagia Outcomes in Anchored Spacers Versus Plate-Screw Systems in Anterior Cervical Discectomy and Fusion: A Systematic Review. Issue 8 (December 2020) - Gabr, Mostafa A.; Touko, Elisabeth; Yadav, Amol P.; Karikari, Isaac; Goodwin, C. Rory; Groff, Michael W.; Ramirez, Luis; Abd-El-Barr, Muhammad M.
Study Design: Systematic review and meta-analysis. Objective: To perform a systematic review of clinical outcomes between stand-alone anchored spacers and traditional cages with plate fixation for dysphagia and pseudoarthrosis using data from clinical trials. Methods: Our search protocol was added to PROSPERO register and systematic review using PRISMA method was performed. Then, we systematically searched for studies addressing stand-alone anchored spacers in patients who underwent ACDF. Mean Neck Disability Index (NDI), dysphagia incidence % (Dinc%), and Swallowing–Quality of Life (SQOL) scores during preoperative, immediate postoperative and last follow-up visits were extracted. Chi-square and analysis of variance (ANOVA) tests were used for statistical comparisons ( P ≤ .05). Results: The initial search generated 506 articles in CENTRAL and 40 articles in MEDLINE. Finally, 14 articles were included. Total number of patients was 1173 (583 anchored stand-alone and 590 plate). Dinc% scores were statistically significantly lower in the stand-alone anchored spacer compared to the plate-screw construct ( P ≤ .05). ANOVA showed no statistically significant difference in the comparisons of SQOL. On the other hand, NDI scores were statistically significantly lower in baseline of stand-alone anchored spacer and the plate-screw construct compared with both immediate postoperative and last follow-up visits ( P ≤ .05). Conclusions: Our study results revealed that the stand-alone anchored spacers were associated with less dysphagia in the immediate and last follow-up.